Effectiveness of self healing in repair of strategic concrete structures "a simplified model" - Fawzy, Mohamed Hussein (AUC Knowledge Fountain, 2017)
Concrete cracking has various causes and is unavoidable. Cracking has adverse effects on structure's integrity, durability and serviceability. In strategic structures such as nuclear reactors and dams this cannot be tolerated, this means that strategic structures should be under a continuous process of inspection and repair. This process has many drawbacks as it is costly, tiring and not sustainable, also it cannot be 100% trusted that the inspection is carried out on time and with enough accuracy. Moreover shutting down any of the strategic structures for the purpose of repair would negatively impact the economy. The addition of self-healing capsules to concrete for the aim of crack recovery is a new promising technique that can be used in strategic structures to minimize the need for inspection and repair. Although a fair amount of research has been carried out to prove that the addition of self-healing capsules to concrete is effective in the sealing of cracks no research has been carried out to investigate if this method is cost effective. The aim of this study is to develop a model that predicts the rate of crack propagation in self-healing concrete and compare it to conventional concrete through a five year period assuming 12 different initial crack areas and also to compare the final cost of using the self-healing concrete versus that of conventional concrete taking factors like cost of repair, type of repair, cost of inspection, cost of disruption and the time value for money in each case into account. This was done through three what if scenarios assuming concrete cracking starts immediately after hardening or after a period of five years have passed and finally if cracking starts after 10 years and through a period of five years. This work gave a promising insight showing that the expected final crack areas were smaller in case of self-healing concrete if no repair takes place and lower costs in all scenarios in case of intervening to carry out repair works. It is recommended to expand this work by taking factors that affect the healing percentages into account.